Level Literasi Digital Peserta Kelas Whatsapp Group Klinik MPASI - Nunik Hariyanti; Mufid Salim; Rifdah Zulfa Ghina Nabilah (Jurnal Komunikasi, 2021)
Abstract. This study aims to explain digital literacy of WhatsApp Group participants of MPASI (complementary feeding) Clinic. This study applied positivism paradigm with a quantitative-descriptive approach. The respondent were participants of WhatsApp MPASI clinic group. Participants fill out a questionnaire that has been compiled based on the digital competency instrument on Network of Digital Literacy Activists (JAPELIDI). The results showed the literacy of this group were at moderate level with 74% of respondents and the remaining 13% at high and low levels. Participants of the MPASI Clinic who also act as digital immigrant. This means they are able to cope with invalid information because of the sufficient knowledge.Keywords: Digital Literacy, Whatsapp Group, Digital Immigrant